Revisiting the cloud: reintegrating the G Suite for Education in English for Specific Purposes teaching - Kakoulli-Constantinou, Elis (My University, 2019)
In an era of continuous technological advancement and severe financial crisis, the cloud computing paradigm has become one of the most prominent and influential developments in information technology since the emergence of the Internet. This chapter describes the second phase of an action research study, which aimed at addressing the problem of lack of appropriate technology tools for the delivery of two blended English for Academic Purposes (EAP) courses for first-year students of the Departments of (1) Agricultural Sciences, Biotechnology, and Food Science and (2) Commerce, Finance, and Shipping, at the Cyprus University of Technology. The solution suggested involved the integration of the G Suite for Education2 in the teaching and learning process. The suite was firstly introduced in the academic year 2016-2017 (Kakoulli Constantinou, 2018), and the feedback obtained then was valuable for its reintegration the following year. The present chapter focusses on the second attempt to integrate the suite in the context of which data was elicited in order to improve the use of the suite for the delivery of the two EAP courses in the future.